PEMAHAMAN HADIS LARANGAN BERBICARA KETIKA DI KAMAR MANDI (STUDI VALIDITAS DALAM KITAB AT-TARGHIB WA AT-TARHIB KARYA AL-MUNDZIRI) - Etika Noviyanti; Uswatun Hasanah; Sulaiman M. Nur (Al-Shamela : Journal of Quranic and Hadith Studies, 2023)
This article aims to examine the validity of the hadith regarding the prohibition of talking while in the bathroom in al-Mundziri's At-Targhib Wa At-Tarhib". By using content analysis and the takhrij al-hadith approach, this article concludes that: first, the quality of the hadith that prohibits speaking while in the bathroom has the quality of a weak sanad and the content of the material is of authentic quality. Therefore, there were no irregularities or defects in the matan of the hadith, so that this hadith can be used as a guide for the wider community in ethics when in the bathroom. Second, al-Mundziri's understanding of this hadith is explained as tarhib (threats, prohibitions, bad replies), by looking at the contextuality of the actions that humans commit when they are in the bathroom. Al-Mundziri directs to the wrath of Allah SWT and his curse as a reward if this is done in a dirty place, and provides a lesson that in Islam in every aspect of life that is carried out there are rules and procedures that have been shown by the Prophet Muhammad SAW.